2010
DOI: 10.1007/s00360-010-0505-7
|View full text |Cite
|
Sign up to set email alerts
|

Muscle plasticity in hibernating ground squirrels (Spermophilus lateralis) is induced by seasonal, but not low-temperature, mechanisms

Abstract: During hibernation, ground squirrels (Spermophilus lateralis) show unusually altered expression of skeletal muscle myosin heavy-chains. Some muscle groups show transitions from fast to slower myosin isoforms despite atrophy, which are not predicted from other mammalian studies of inactivity. We measure myosin protein and mRNA expression, and the mRNA expression of genes important in atrophy and metabolism in a time-course of muscle plasticity prior to, and during extended hibernation. We also investigate the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
77
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(91 citation statements)
references
References 84 publications
13
77
1
Order By: Relevance
“…These findings suggest that Weddell seals may be physiologically "programmed" to withstand periods of reduced activity while maintaining muscle integrity. Wild animals may need to forage effectively and escape predation after such periods of reduced activities, and indeed, similar patterns of atrophy resistance have been observed in hibernating bats and rodents, and winter lethargy in bears (Lohuis et al 2007;Hershey et al 2008;Lee et al 2008;Nowell et al 2011). Despite being composed of primarily slow-oxidative fibers that are particularly vulnerable to atrophy, Weddell seal muscles maintained aerobic MHC profiles.…”
mentioning
confidence: 65%
“…These findings suggest that Weddell seals may be physiologically "programmed" to withstand periods of reduced activity while maintaining muscle integrity. Wild animals may need to forage effectively and escape predation after such periods of reduced activities, and indeed, similar patterns of atrophy resistance have been observed in hibernating bats and rodents, and winter lethargy in bears (Lohuis et al 2007;Hershey et al 2008;Lee et al 2008;Nowell et al 2011). Despite being composed of primarily slow-oxidative fibers that are particularly vulnerable to atrophy, Weddell seal muscles maintained aerobic MHC profiles.…”
mentioning
confidence: 65%
“…James et al (James et al, 2013) reported no loss of mass or tension in soleus muscle of S. tridecemlineatus following three months of hibernation, whereas a 14% loss was found in the gastrocnemius and 43% loss in the semitendinous muscles of the golden-mantled ground squirrel (Spermophilus lateralis) (Wickler et al, 1991). Muscle atrophy develops early on in hibernating S. lateralis but does not advance in the final 3 months (Nowell et al, 2011), a result which is similar to that which occurs during prolonged bed rest in humans (Adams et al, 2003;Phillips et al, 2009). …”
Section: Hibernating Mammals As Models Of Muscle Disuse Atrophymentioning
confidence: 99%
“…Brooks and coworkers demonstrated that myostatin protein levels in mixed hindlimb muscle of S. tridecemlineatus were largely constant throughout torpor relative to controls, but increased significantly during arousal (Brooks et al, 2011) while in hibernating S. lateralis, a significant reduction in myostatin gene expression was found in soleus and diaphragm muscles, but not in limb muscles with fast-type fibres (Nowell et al, 2011 …”
Section: Hibernating Mammals As Models Of Muscle Disuse Atrophymentioning
confidence: 99%
See 2 more Smart Citations